Induction of central nervous system plasticity by repetitive transcranial magnetic stimulation to promote sensorimotor recovery in incomplete spinal cord injury - Ellaway, Peter H.; Vásquez, Natalia; Craggs, Michael (Frontiers in Integrative Neuroscience, 2014)
Cortical and spinal cord plasticity may be induced with non-invasive transcranial magnetic stimulation to encourage long term potentiation or depression of neuronal circuits. Such plasticity inducing stimulation provides an attractive approach to promote changes in sensorimotor circuits that have been degraded by spinal cord injury (SCI). If residual corticospinal circuits can be conditioned appropriately there should be the possibility that the changes are accompanied by functional recovery. This article reviews the attempts that have been made to restore sensorimotor function and to obtain functional benefits from the application of repetitive transcranial magnetic stimulation (rTMS) of the cortex following incomplete spinal cord injury. The confounding issues that arise with the application of rTMS, specifically in SCI, are enumerated. Finally, consideration is given to the potential for rTMS to be used in the restoration of bladder and bowel sphincter function and consequent functional recovery of the guarding reflex.